If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34 + -3x = 6x + -2 Reorder the terms: 34 + -3x = -2 + 6x Solving 34 + -3x = -2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 34 + -3x + -6x = -2 + 6x + -6x Combine like terms: -3x + -6x = -9x 34 + -9x = -2 + 6x + -6x Combine like terms: 6x + -6x = 0 34 + -9x = -2 + 0 34 + -9x = -2 Add '-34' to each side of the equation. 34 + -34 + -9x = -2 + -34 Combine like terms: 34 + -34 = 0 0 + -9x = -2 + -34 -9x = -2 + -34 Combine like terms: -2 + -34 = -36 -9x = -36 Divide each side by '-9'. x = 4 Simplifying x = 4
| 4n+7=6n+1 | | 3x+4-6x=7 | | 10p^2+60p=50 | | 0.04(y-5)+0.12y=0.20y-0.6 | | 6x-5-3x=-2 | | 12-x=2x+3 | | logx=100 | | -7(x-6)-2=40 | | 3/2x^2-8x+8 | | 5x-2-2x=-8 | | a/5+5=5/2 | | 4x+4-6x=-8 | | x^(1/2)-4=0 | | 1/2x^3-4x^2+8x | | 4x-7-6x=-5 | | 2+6x=-58 | | 4x+6-5x=3 | | (x^1/2)-4=0 | | s^2+3s-4=0 | | x^2+19=14x | | c=2p-5q | | 4x+3-3x=9 | | 12-10x=72-32x | | -20-9x=49-23x | | X^2+14x-15=o | | 5/6*8/15 | | 3x-4x=10+7x-3 | | 5/6x8/15 | | 4(x-7)=3(x+3) | | 12-x=0 | | 1(2)=3x+11 | | 6x+4-3x=-2 |